(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2016)
A study was carried out on taxonomic record and distribution pattern of the freshwater apple snail, Pila glogosa from January 1995 to December 1996 in different waterbodies of Rajshahi University Campus. In total, 27 generic and 21 species names were recorded including the valid name Pila globosa (Swaindon, 1822). The shell of P. gloosa is thick and globose. The spire is not acuminate and shorter than the body whorl. The apple snail was found to occur in tanks, ponds, ditches and irrigated paddy fields of Rajshahi University Campus, Rajshahi. The apple snail prefered littoral zones of ponds and ditches but shore lines of canals and irrigated paddy fields. Aestivation of the apple snsails took place with the total water loss of the habitats. Bangladesh J. Sci. Ind. Res. 51(4), 313-318, 2016